2012
DOI: 10.12968/bjcn.2012.17.11.512
|View full text |Cite
|
Sign up to set email alerts
|

A silent epidemic: community nursing and effective pain management

Abstract: Effective pain management presents challenges to health care practitioners, particularly in the community setting. This is evident from the complexities associated with the phenomenon of pain and the circumstances for those patients suffering from pain. An overwhelming amount of literature and research surrounding pain exists in an effort to improve our understanding of pain, assessment and management strategies. But patients in pain are not managed well in the community or acute setting. Health care professio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…In addition, FCNs provide tertiary health care, supporting patients, families, and communities in illness management in different clinical settings, such as vascular disease management [ 65 ], psoriasis and eczema [ 18 , 66 ], fibromyalgia [ 67 ], arthritis [ 68 , 69 ], and chronic pain [ 70 , 71 ]. Review results have demonstrated how FCNs face challenges in the entire community in tertiary health care, especially for particular and fragile categories [ 72 , 73 , 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, FCNs provide tertiary health care, supporting patients, families, and communities in illness management in different clinical settings, such as vascular disease management [ 65 ], psoriasis and eczema [ 18 , 66 ], fibromyalgia [ 67 ], arthritis [ 68 , 69 ], and chronic pain [ 70 , 71 ]. Review results have demonstrated how FCNs face challenges in the entire community in tertiary health care, especially for particular and fragile categories [ 72 , 73 , 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among European countries, Italy ranks first in the clinical use of nonsteroidal anti-inflammatory drugs (NSAIDs) and at the bottom for opiate use [ 13 ]. Despite the existence of evidence-based guidelines for the appropriate management of pain, many patients still suffer from inadequate pain treatment [ 14 , 15 ]. Cultural barriers negatively affect the management of pain [ 14 ]; these barriers include the educational training of healthcare professionals, including physicians and nurses, and correct patient information [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the existence of evidence-based guidelines for the appropriate management of pain, many patients still suffer from inadequate pain treatment [ 14 , 15 ]. Cultural barriers negatively affect the management of pain [ 14 ]; these barriers include the educational training of healthcare professionals, including physicians and nurses, and correct patient information [ 16 ]. Healthcare providers also play a fundamental role in the initial evaluation of pain, the short-term control of pain, the analgesic effect of treatment, long-term follow-up, and the satisfaction of patients suffering from pain [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The involvement of FCNs in health promotion, including primary, secondary and tertiary prevention, has been widely reported in the recent literature [10]. Concerning the prevention of long-term disabilities, FCNs support patients, families and communities in disease management, such as vascular and neurological issues [55,56], diabetes [57], chronic heart failure [58] and chronic pain management [59,60]. Through prompt detection, the FCN can ensure that the health problems of older citizens with long-term and chronic conditions are treated early, fostering complication management and hospital avoidance [61].…”
Section: Discussionmentioning
confidence: 99%